2022
DOI: 10.1155/2022/4897201
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding XLOC_006390 Regulates the Proliferation and Metastasis of Human Colorectal Cancer via miR-296/ONECUT2 Axis

Abstract: Long noncoding RNA (LncRNA) XLOC_006390 has been shown to be dysregulated in cancer tissues and regulates cancer growth and development. Nonetheless, the molecular role of lncRNA-XLOC_006390 in colorectal cancer via modulation of miR-296/ONECUT2 axis is still unclear. Against this backdrop, the current study was designed to explore the role of lncRNA-XLOC_006390 in colorectal cancer proliferation and metastasis. The results revealed significant ( P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…The silencing of SPINT1-AS1 mediates the expression of HDGF by targeting miR-214, increasing apoptosis in CRC cells ( 193 ). Ma et al.’s study reveals that silencing XLOC_006390 inhibits apoptosis in CRC through the regulation of the miR-296/ONECUT2 axis ( 207 ). Fang et al.…”
Section: Lncrnas Regulate Cell Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…The silencing of SPINT1-AS1 mediates the expression of HDGF by targeting miR-214, increasing apoptosis in CRC cells ( 193 ). Ma et al.’s study reveals that silencing XLOC_006390 inhibits apoptosis in CRC through the regulation of the miR-296/ONECUT2 axis ( 207 ). Fang et al.…”
Section: Lncrnas Regulate Cell Apoptosismentioning
confidence: 99%
“…reported that downregulation of XIST inhibits migration and invasion in CRC cells by regulating the miR-338-3p/PAX5 axis ( 205 ). The silencing of XLOC006390 significantly inhibits their viability by inducing apoptosis and limiting the migration and invasion of cancer cells ( 207 ). Fang et al.’s study shows that ZFAS1 promotes CRC invasion, and its mechanism is associated with E-cadherin, ZO-1, vimentin, and N-cadherin ( 208 ).…”
Section: Lncrnas Regulate Invasion and Metastasismentioning
confidence: 99%